2008
DOI: 10.3844/ajabssp.2008.656.660
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Agro-Climatologically Variables to Identify Suitable Areas for Rapeseed in Different Dates of Sowing by GIS approach

Abstract: Abstract:The study carried out in tow provinces (Isfahan and Chaharmahal va Bakhtyiari), central and southwest, Iran. The study area covers approximately 37659 Km 2 of total area. This area is located between latitude 30° 42′ N and 33° 37′ N and between longitude 49° 56′ W and 51° 57′ W. The climate variables taken into account were maximum and minimum daily average temperature, Growth Degree Day (GDD) between four dates of sowing to physiological maturity and four dates sowing to freezing start day (rosette),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Optimal cropping patterns for the flood and post flood season based on crop suitability and expert knowledge indicated that the rice-wheat/potato, rice (late sowing)-potato, rice-potato and rice-mustard combinations were found the most suitable suggested pattern for the study area [13]. Ghasemi Pirbalouti and Golparvar [14] evaluated agro climatologically variables to identify suitable areas for rapeseed in different dates of sowing by GIS. This study carried out in two provinces (Isfahan and Chaharmahal va Bakhtyiari), central and southwest of Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal cropping patterns for the flood and post flood season based on crop suitability and expert knowledge indicated that the rice-wheat/potato, rice (late sowing)-potato, rice-potato and rice-mustard combinations were found the most suitable suggested pattern for the study area [13]. Ghasemi Pirbalouti and Golparvar [14] evaluated agro climatologically variables to identify suitable areas for rapeseed in different dates of sowing by GIS. This study carried out in two provinces (Isfahan and Chaharmahal va Bakhtyiari), central and southwest of Iran.…”
Section: Introductionmentioning
confidence: 99%